Fashion clothing for disable persons - Matos, Adriana Leiria Barreto (2008)
Development of fashion clothing combining ergonomical and psychological comfort is a need for disabled persons. From the users’ point of view the product must also address aesthetic aspects such as fashion trends. Considering the social connotation that fashion has, it was decided to work in the conception of clothes developed for persons with physical disability. Having also in mind the diversity and specificity of the existent cases and the special demand of each one, particularly whose suffer poliomyelitis sequels and other diseases that cause the use of prosthetics in the legs and crutches for walking. This last group was selected as the target-market.